2020
DOI: 10.3390/children7070070
|View full text |Cite
|
Sign up to set email alerts
|

Drowning in Children: Retrospective Analysis of Incident Characteristics, Predicting Parameters, and Long-Term Outcome

Abstract: Background: Drowning is the second leading cause of unnatural death in childhood worldwide. More than half of the drowned children, who were in need of cardiopulmonary resuscitation (CPR) at the scene suffered from lifelong neurological sequelae. There are few data about prognostic predictors in the pediatric population of drowning victims. The objective of the study was to assess incident characteristics, prognostic parameters, and long-term outcome of children recovering from a drowning incident. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 55 publications
(94 reference statements)
4
18
3
Order By: Relevance
“…In this study children were in the high-risk group, and the highest frequency referred to two-year-old children. Almost similar results were found in a study held in Ireland by Davey et al showed that the majority of drowning cases affected children between the ages of 1-4 ( 8 ), other studies held by Evans et al ( 9 ), Denny et al ( 10 ), Wang et al ( 11 ), and Raess et al ( 12 ) showed that drowning mostly affected children under the age of 5 which comes in agreement with our findings. This result may have been caused by the absence of children strict supervision.…”
Section: Discussionsupporting
confidence: 93%
“…In this study children were in the high-risk group, and the highest frequency referred to two-year-old children. Almost similar results were found in a study held in Ireland by Davey et al showed that the majority of drowning cases affected children between the ages of 1-4 ( 8 ), other studies held by Evans et al ( 9 ), Denny et al ( 10 ), Wang et al ( 11 ), and Raess et al ( 12 ) showed that drowning mostly affected children under the age of 5 which comes in agreement with our findings. This result may have been caused by the absence of children strict supervision.…”
Section: Discussionsupporting
confidence: 93%
“…Fortunately, only a minority (<2%) require hospital admission [ 13 ]. Vital emergencies and cardiorespiratory arrest (CRA) can happen anywhere, with drowning being the second leading cause of unnatural childhood death worldwide [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…8 Research has found that even a brief lapse in supervision to take a phone call is long enough for a drowning to occur. [16][17][18] Caregivers we interviewed agreed that the smartphone application would help to remove the temptation to use their cell phones while supervising and would create a concrete cue to action that they could envision having an impact on their behaviour.…”
Section: Discussionmentioning
confidence: 99%